Energy and environmental characteristics of coal and biocomponents co-combustion; Energy; Vol. 340 - Dorokhov V. V. Vadim Valerjevich; Vershinina K. Yu. Kseniya Yurievna; Kartashova K. A. Kseniya Andreevna; Kovtunets I. S. Igor Stanislavovich; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen